The Program Kemitraan Masyarakat Pencegahan Stunting dengan Pemberian Produk Olahan Susu Kelompok Murid TK GMIM Kanaan Kalvari Kasuratan Kabupaten Minahasa: Community Partnership Program Stunting Prevention by Providing Dairy Products on Kindergarten Students at TK GMIM Kanaan Kalvari Kasuratan Minahasa Regency (Tumou Tou: Jurnal Pengabdian Masyarakat, 2022)
Stunting is such a complex problem that is happening globally, in regions, and even in developing countries. Considering that stunting is a serious and dangerous health-problem, it is important to understand and take precautions or else it might damage the upcoming generation weaken human resources, and inadequate quality of health and intelligence in more dangerous cases death might happen. This community partnership program aims to hold stunting prevention by providing dairy products such as fresh milk that contain proteins, carbohydrates, fats and vitamins to kindergarten students at TK GMIM Kanaan Kalvari Kasuratan, Minahasa Regency hoping that this might help the population to improve the quality of children health. Methods that are used in this program were counseling and guidance health-related, promoting stunting prevention as well as demonstrations by giving milk to kindergarten students. The result showed a good response and appreciation from the community as we found the enthusiasm of the participants who had been active while receiving oral presentation by the whole team. Keywords:partnership; stunting; fresh milk; dairy products